Domains which are locally uniformly linearly convex in the Kobayashi distance - Monika Budzyńska (Abstract and Applied Analysis)
We show a construction of domains in complex reflexive Banach spaces which are locally uniformly convex in linear sense in their Kobayashi distance. We also show connections between norm and Kobayashi distance properties.